Digital image analysis of root distribution towards improved irrigation water and soil management: Grapevine and date palm study cases - Bassoi, Luís Henrique [UNESP]; Moura E Silva, José Antonio; De Alencar, Cristina Miranda [UNESP]; De Castro Jorge, Lúcio André; Hopmans, Jan W. (My University, 2000)
It is presented two study cases about the approach in root analysis at field and laboratory conditions based on digital image analysis. Grapevine (Vitis vinifera L.) and date palm (Phoenix dactylifera L.) root systems were analyzed by both the monolith and trench wall method aided by digital image analysis. Correlation between root parameters and their fractional distribution over the soil profile were obtained, as well as the root diameter estimation. Results have shown the feasibility of digital image analysis for evaluation of root distribution.
Keywords: Image analysis; Phoenix dactylifera L.; Root distribution; Vitis vinifera L.; Coloring; Crops; Parameter estimation; Plants (botany); Soils; Sprinkler systems (irrigation); Phoenix dactylifera L; Vitis vinifera L; Irrigation